Solid-phase synthesis of chiral 3,4-diazaphospholanes and their application to catalytic asymmetric allylic alkylation - Landis, Clark R. (National Academy of Sciences, 2004)
Functionalized chiral diazaphospholanes ligate to a variety of transition metals, yielding chiral, catalytically active, metal complexes. Previous work has established that amino acid derivatization of the carboxyl groups of (R,R)-N,N′-phthaloyl-2,3-(2-carboxyphenyl)-phenyl-3,4-diazaphospholane (1) yields phosphines that are excellent ligands for palladium-catalyzed asymmetric allylic alkylation reactions. Alanine functionalization is particularly effective for allylic alkylation of 1,3-dimethylallyl acetate. Standard Merrifield resins and amino acid coupling methods are used to synthesize the bead-attached phosphine having the topology bead-linker-lAla-(R,R)-1-lAla-OMe, as a 1:1 mixture of linkage isomers. Use of this supported phosphine in Pd-catalyzed asymmetric allylic alkylation yields 92% enantiomeric excess, matching prior solution-phase results. A 20-member collection of amino acid-functionalized phosphines on beads with the topology bead-linker-AA(2)-AA(1)-1-AA(1)-AA(2) was synthesized by using parallel solid-state methods and screened for efficacy in allylic alkylation. Resulting enantioselectivities indicate that the AA(1) position has the strongest effect on the reaction. Catalyst activities can vary widely with the nature of the phosphine ligand and the reaction conditions. Meaningful analysis of intrinsic catalytic activities awaits identification of the structure and abundance of the active catalyst.